Vertical Root Fracture: Preservation of the Alveolar Ridge Using Immediate Implants. (12th March 2014) - Oya, Edmar de Oliveira; Pallos, Debora; Schwartz-Filho, Humberto Osvaldo; Brandt, William Cunha; Sendyk, Wilson Roberto; Roman-Torres, Caio Vinicius Gonçalves
Abstract : Teeth with vertical root fracture (VRF) have complete or incomplete fractures that begin in the root and extend toward the occlusal surface. The most frequent causes of VRF originate from physical trauma, occlusal prematurity, inadequate endodontic treatment, and iatrogenic causes. Diagnose is difficult and delay can cause stomatognathic system problem. The purpose of this case report was to evaluate immediate implant placement after extraction of teeth with vertical root fracture. For the 1st case, the VRF in 1st left lower molar was confirmed during surgical flap and at the same time, the tooth was removed and immediate implant was placed. For the 2nd case, the VRF 1st left lower molar was confirmed during endodontic access and at the same appointment, the tooth was removed and the immediate implant is placed. Several studies have shown that immediate implants have similar success rates when compared with late implants. Consider that this approach is a safe procedure with favorable prognosis. In cases of VRF, the main factor to be considered is the presence of adequate bone support and immediate implants can preserve the vertical bone height, adding the fact that good patient compliance reduces the number of surgical interventions and promotes the functionality of stomatognathic system.